Black swans and fat tails. (Economist, 2019)
The article deals with the challenges facing insurers in meeting the growing demand for cyber-insurance amidst several cases of high-profile hacks. Topics covered include outlook of information technology (IT) bosses on their preparedness for a cyberattack, overview of high-profile hacks like the theft of customer records of Starwood, a hotel chain owned by Marriott International, and vagueness of the currently available cyber-insurance policies.